Electrolytic copper foil surface treatment process

Through the surface treatment process of electrolytic copper foil, including degreasing, coarsing, curing, barrier layer treatment, surface antioxidant impregnation and organic protective agent spraying, the problem of insufficient antioxidant properties and wear resistance of electrolytic copper foil is solved, and the problem of insufficient anti-oxidation performance and wear resistance of electrolytic copper foil is significantly improved Its service life and quality.

CN119121243AActive Publication Date: 2024-12-13GUANGDONG FINE YUAN SCI TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411284704.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-13
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The existing electrolytic copper foil has poor oxidation resistance and wear resistance, which affects its service life and quality.

Method used

The surface layer is prepared by the Zn-Ni-K ternary alloy treatment process and cross-linking reaction using a surface treatment process, including degreasing, coarsing, curing, forming a barrier layer, impregnating the surface antioxidant liquid and spraying organic protective agent. Antioxidant liquid and organic protective agent form a dense antioxidant protective film and protective film.

Benefits of technology

It significantly improves the oxidation resistance and wear resistance of electrolytic copper foil, extends the service life and improves the quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005042792200000101
    Figure BDA0005042792200000101
Patent Text Reader

Abstract

The invention relates to the technical field of electrolytic copper foils, in particular to an electrolytic copper foil surface treatment process. A coupling agent is added into a thiamine chloride pyrophosphate aqueous solution, a glutaraldehyde aqueous solution is added into the thiamine chloride pyrophosphate aqueous solution while stirring after heating treatment, then liquid in a reaction product is completely evaporated after a heat preservation reaction, and finally reactants are subjected to a cross-linking reaction under the bridge action of the coupling agent, so that the thiamine chloride pyrophosphate is obtained. Uniformly mixing the obtained solid powder with acetone to obtain surface layer anti-oxidation liquid; the copper foil is soaked in the prepared surface layer anti-oxidation liquid, a compact anti-oxidation protection film layer can be formed on the surface of the copper foil, the anti-oxidation performance of the electrolytic copper foil is effectively improved, finally, under the double-effect cooperation of the surface layer anti-oxidation liquid and the organic protective agent, the anti-oxidation performance of the electrolytic copper foil is further guaranteed, and the service life of the electrolytic copper foil is prolonged. And meanwhile, the wear resistance of the electrolytic copper foil is also improved, the service life of the electrolytic copper foil is prolonged to a certain extent, and the quality of the electrolytic copper foil is also remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrolytic copper foil, in particular to a surface treatment process of electrolytic copper foil. Background Art

[0002] Electrolytic copper foil refers to making copper raw materials into copper sulfate solution, and then using electrolytic equipment to make the solution electrodeposited into copper foil under the action of direct current. Electrolytic copper foil is an important material for copper clad laminate (CCL), printed circuit board (PCB), and lithium-ion battery manufacturing. According to the thickness of copper foil, it can be divided into ultra-thin copper foil (≤6m), ultra-thin copper foil (6-12m), thin copper foil (12-18m), conventional copper foil (18-70m) and thick copper foil (>70m) according to the prevailing standards; according to the surface conditions, it can be divided into double-sided smooth copper foil, double-sided rough copper foil, double-sided treated copper foil, single-sided rough copper foil and low-profile copper foil (RTF copper foil, VLP copper foil, HVLP copper foil), etc.

[0003] The patent document with application number "CN200710126403.0" discloses a surface-treated electrolytic copper foil, a method for manufacturing the same, and a circuit board. In the surface-treated electrolytic copper foil, the M surface, which is the surface opposite to the surface in contact with the drum, is surface-treated, and the Rz of the M surface is less than 1.0 μm, and the Ra is less than 0.2 μm. The surface-treated electrolytic copper foil is manufactured by the following method for manufacturing the surface-treated electrolytic copper foil: copper foil is manufactured by electrolytic copper plating using a copper sulfate bath at a current density of 20 to 50 A / dm2.

[0004] Although the electrolytic copper foil prepared in the above patent document has the advantages of smooth surface and easy identification, its own anti-oxidation performance and wear resistance are relatively poor, which to a certain extent affects the service life of the electrolytic copper foil, and also affects its quality. Based on this, the present invention provides a surface treatment process for electrolytic copper foil! Summary of the invention

[0005] The purpose of the present invention is to provide a surface treatment process for electrolytic copper foil, wherein the treated electrolytic copper foil not only has excellent anti-oxidation performance, but also has excellent wear resistance, which prolongs the service life of the electrolytic copper foil to a certain extent and also significantly improves its quality.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A surface treatment process for electrolytic copper foil comprises the following steps:

[0008] Step 1: Place the copper foil in a degreasing tank, and add a sodium hydroxide aqueous solution with a temperature of 55-65°C and a concentration of 60-75 g / L into the tank to clean and degrease the copper foil; after degreasing, wash with water, and then pickle the copper foil. After pickling, place the copper foil in a water washing tank to clean its surface;

[0009] Step 2: Place the copper foil treated in step 1 in a roughening tank for roughening treatment. After the roughening is completed, place the copper foil in a water washing tank for washing. 2+ The concentration of H2SO4 is 15-30 g / L, the concentration of H2SO4 is 130-150 g / L, the temperature is 30-45 °C, and the electrolyte flow rate is 13-18 m 3 / h;

[0010] Step 3: Place the copper foil roughened in step 2 in a curing tank for curing. After curing, place the copper foil in a water washing tank for washing. 2+ The concentration is 55-75 g / L, the H2SO4 concentration is 110-130 g / L, the temperature is 30-50 °C, and the electrolyte flow rate is 15-20 m 3 / h;

[0011] Step 4: Place the solidified copper foil in a barrier layer treatment tank, and use a Zn-Ni-K ternary alloy treatment process to form a barrier layer on the surface of the copper foil; after water washing, immerse the copper foil in a surface antioxidant liquid at a temperature of 50 to 65° C. for 5 to 10 minutes;

[0012] Step 5: After the impregnation is completed, the copper foil is fished out and cleaned with anhydrous ethanol, and then the copper foil is transferred to a vacuum drying oven and vacuum dried at a temperature of 70 to 90°C;

[0013] Step 6: After vacuum drying is completed, spray the organic protective agent evenly on the surface of the copper foil and dry it at a temperature of 60-80°C; after drying is completed, cut and package the copper foil in turn; finally, the surface treatment process of the electrolytic copper foil is completed.

[0014] Furthermore, the acid solution used in step 1 is a 110-130 g / L aqueous sulfuric acid solution, and its temperature is 30-50°C.

[0015] Furthermore, in the step 2, when the copper foil is roughened, the roughening current is set to 2900-3200A, and the roughening time is set to 4-7s.

[0016] Furthermore, in the step three, when the copper foil is cured, the curing current is set to 2300-2700A, and the curing time is set to 5-8s.

[0017] Furthermore, in the step 4, when forming the barrier layer, Zn 2+ The concentration is 2-3 g / L, Ni 2+ The concentration is 1.5-2 g / L, K + The concentration is 90~110g / L.

[0018] Furthermore, the preparation method of the surface antioxidant liquid is as follows: adding a coupling agent with a mass of 0.4 to 0.5 times that of thiamine chloride pyrophosphate to a 35 to 45 g / L aqueous solution of thiamine chloride pyrophosphate, mixing and stirring evenly, heating to 75 to 85° C., and then slowly dropping a glutaraldehyde aqueous solution with a mass of 1.5 to 2.5 times that of the coupling agent and a concentration of 20 to 25% into the obtained mixed solution while stirring; after the dropwise addition is completed, the reaction is kept warm for 4 to 6 hours. After the reaction is completed, the liquid in the reaction product is completely evaporated, and the obtained solid powder is put into 7 to 10 times the mass of acetone, and mixed and stirred evenly to obtain the surface antioxidant liquid.

[0019] Furthermore, the coupling agent is selected from any one of γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane and γ-aminopropylmethyldiethoxysilane.

[0020] Furthermore, the preparation method of the organic protective agent comprises the following steps:

[0021] The first step is to add 0.6 to 0.8 times the mass of butanol aldehyde into a 4 to 6 wt % ether solution of butanol aldehyde, add concentrated hydrochloric acid after mixing and stirring evenly, and react the resulting mixed components at a temperature of 120 to 130° C. for 8 to 12 hours. After the reaction is completed, the resulting components are subjected to rotary evaporation, and the resulting reaction products are stored and reserved;

[0022] Step 2: Add 1.05-1.1 times the mass of the reaction product to a 0.05-0.08 g / mL chloroform solution of 5-methyl-1H-benzotriazole, raise the temperature to 60-70°C and stir to fully dissolve it, then slowly drip 1.4-1.5 times the mass of 5-methyl-1H-benzotriazole toluene-2,4-diisocyanate while stirring, and keep the temperature for 50-70 minutes after the addition is complete;

[0023] Step 3: After the reaction is completed, add a 30-40% volume of hydrochloric acid aqueous solution with a concentration of 2-4 mol / L to the resulting component, and keep the reaction at a temperature of 45-55°C for 5-7 hours; after the reaction is completed, perform rotary evaporation on the resulting component; then mix the resulting liquid composition with anhydrous ethanol in a volume ratio of 1:4-6, and obtain an organic protective agent after mechanical stirring.

[0024] Furthermore, the concentration of concentrated hydrochloric acid in the first step is 36-38 wt %, and the amount of concentrated hydrochloric acid used is 0.4-0.5 times the volume of ether.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. In the present invention, a coupling agent is added to an aqueous solution of thiamine chloride pyrophosphate, and a glutaraldehyde aqueous solution is added thereto while stirring after a temperature treatment, and then the liquid in the reaction product is completely evaporated after a heat preservation reaction, and finally the reactants undergo a cross-linking reaction under the "bridge" effect of the coupling agent, and the obtained solid powder is mixed with acetone to obtain a surface antioxidant liquid. The copper foil is immersed in the obtained surface antioxidant liquid to form a dense antioxidant protective film layer on the surface of the copper foil, which can effectively improve the antioxidant performance of the electrolytic copper foil.

[0027] 2. In the present invention, ethylene glycol is added to the ether solution of butanol aldehyde, concentrated hydrochloric acid is added after mixing and stirring, and the obtained reaction product is added to the chloroform solution of 5-methyl-1H-benzotriazole after heat preservation reaction and rotary evaporation treatment, and toluene-2,4-diisocyanate is slowly added thereto while stirring, and hydrochloric acid aqueous solution is added to the obtained product component after heat preservation reaction, and after heat preservation reaction and rotary evaporation treatment, the obtained liquid composition is uniformly mixed with anhydrous ethanol to finally prepare an organic protective agent. The prepared organic protective agent is uniformly sprayed on the surface of the copper foil, which can react with the exposed metal copper and form a protective film on the surface of the copper foil. Finally, under the dual-effect synergy of the surface antioxidant liquid and the organic protective agent, not only the antioxidant performance of the electrolytic copper foil is further guaranteed, but also the wear resistance of the electrolytic copper foil is improved, and the service life of the electrolytic copper foil is extended to a certain extent, and its quality is significantly improved. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] A surface treatment process for electrolytic copper foil comprises the following steps:

[0031] Step 1: Place the copper foil in a degreasing tank, and add a sodium hydroxide aqueous solution with a temperature of 55°C and a concentration of 60g / L into the tank to clean and degrease it; after degreasing, wash with water, and then pickle the copper foil. After pickling, place the copper foil in a water washing tank to clean its surface; wherein the acid solution used is a 110g / L sulfuric acid aqueous solution, and its temperature is 30°C;

[0032] Step 2: Place the copper foil treated in step 1 in a roughening tank for roughening treatment. After the roughening is completed, place the copper foil in a water washing tank for washing. 2+ The concentration of H2SO4 is 15g / L, the concentration of H2SO4 is 130g / L, the temperature is 30℃, and the electrolyte flow rate is 13m 3 / h; wherein, when the copper foil is roughened, the roughening current is set to 2900A and the roughening time is set to 4s;

[0033] Step 3: Place the copper foil roughened in step 2 in a curing tank for curing. After curing, place the copper foil in a water washing tank for washing. 2+ The concentration is 55g / L, the H2SO4 concentration is 110g / L, the temperature is 30℃, and the electrolyte flow rate is 15m 3 / h; wherein, when the copper foil is cured, the curing current is set to 2300A and the curing time is set to 5s;

[0034] Step 4: Place the solidified copper foil in a barrier layer treatment tank, and use a Zn-Ni-K ternary alloy treatment process to form a barrier layer on the surface of the copper foil; after water washing, immerse the copper foil in a surface antioxidant liquid at a temperature of 50°C for 10 minutes; when forming the barrier layer, Zn 2+ The concentration is 2g / L, Ni 2+ The concentration is 1.5 g / L, K + The concentration is 90g / L;

[0035] Step 5: After the impregnation is completed, the copper foil is fished out and cleaned with anhydrous ethanol, and then the copper foil is transferred to a vacuum drying oven and vacuum dried at a temperature of 70°C;

[0036] Step 6: After vacuum drying is completed, spray the organic protective agent evenly on the surface of the copper foil and dry it at 60°C; after drying is completed, cut and package the copper foil in turn; finally, the surface treatment process of the electrolytic copper foil is completed.

[0037] The preparation method of the surface antioxidant liquid is as follows: add γ-aminopropyltrimethoxysilane with a mass of 0.4 times that of thiamine chloride pyrophosphate to a 35g / L aqueous solution of thiamine chloride pyrophosphate, stir and mix evenly, heat to 75°C, and then slowly drop a glutaraldehyde aqueous solution with a mass of 1.5 times that of γ-aminopropyltrimethoxysilane and a concentration of 20% into the obtained mixed solution while stirring; after the dropwise addition is completed, heat and react for 4 hours. After the reaction is completed, completely evaporate the liquid in the reaction product, put the obtained solid powder into 7% acetone, mix and stir evenly to obtain the surface antioxidant liquid.

[0038] The preparation method of the organic protective agent comprises the following steps:

[0039] The first step is to add 0.6 times the mass of ethylene glycol to a 4wt% ether solution of butanol aldehyde, mix and stir evenly, then add concentrated hydrochloric acid, and react the resulting mixed components at a temperature of 120°C for 8h. After the reaction is completed, the resulting components are rotary evaporated, and the resulting reaction products are stored for standby use; wherein the concentration of the concentrated hydrochloric acid is 36wt%, and the amount of the concentrated hydrochloric acid used is 0.4 times the volume of the ether;

[0040] Step 2: Add 1.05 times the mass of the reaction product to a 0.05 g / mL chloroform solution of 5-methyl-1H-benzotriazole, raise the temperature to 60°C and stir to fully dissolve it, then slowly drop 1.4 times the mass of 5-methyl-1H-benzotriazole in toluene-2,4-diisocyanate while stirring, and keep the temperature for 50 minutes after the addition is complete;

[0041] Step 3: After the reaction is completed, add a 30% volume of 2 mol / L hydrochloric acid aqueous solution to the resulting component, and keep the reaction at 45°C for 5 hours; after the reaction is completed, perform rotary evaporation on the resulting component; then mix the resulting liquid composition with anhydrous ethanol in a volume ratio of 1:4, and obtain an organic protective agent after mechanical stirring.

[0042] Example 2

[0043] A surface treatment process for electrolytic copper foil comprises the following steps:

[0044] Step 1: Place the copper foil in a degreasing tank, and add a sodium hydroxide aqueous solution with a temperature of 60°C and a concentration of 70g / L into the tank to clean and degrease it; after degreasing, wash with water, and then pickle the copper foil. After pickling, place the copper foil in a water washing tank to clean its surface; wherein the acid solution used is a 120g / L sulfuric acid aqueous solution, and its temperature is 40°C;

[0045] Step 2: Place the copper foil treated in step 1 in a roughening tank for roughening treatment. After the roughening is completed, place the copper foil in a water washing tank for washing.2+ The concentration of H2SO4 is 25g / L, the concentration of H2SO4 is 140g / L, the temperature is 40℃, and the electrolyte flow rate is 15m 3 / h; wherein, when the copper foil is roughened, the roughening current is set to 3000A and the roughening time is set to 5s;

[0046] Step 3: Place the copper foil roughened in step 2 in a curing tank for curing. After curing, place the copper foil in a water washing tank for washing. 2+ The concentration is 65g / L, the H2SO4 concentration is 120g / L, the temperature is 40℃, and the electrolyte flow rate is 15m 3 / h; wherein, when the copper foil is cured, the curing current is set to 2500A and the curing time is set to 6s;

[0047] Step 4: Place the solidified copper foil in a barrier layer treatment tank, and use a Zn-Ni-K ternary alloy treatment process to form a barrier layer on the surface of the copper foil; after water washing, immerse the copper foil in a surface antioxidant liquid at a temperature of 60°C for 8 minutes; when forming the barrier layer, Zn 2+ The concentration is 2.5g / L, Ni 2+ The concentration is 1.5 g / L, K + The concentration is 100g / L;

[0048] Step 5: After the impregnation is completed, the copper foil is fished out and cleaned with anhydrous ethanol, and then the copper foil is transferred to a vacuum drying oven and vacuum dried at a temperature of 80°C;

[0049] Step 6: After vacuum drying is completed, spray the organic protective agent evenly on the surface of the copper foil and dry it at 70°C; after drying is completed, cut and package the copper foil in turn; finally, the surface treatment process of the electrolytic copper foil is completed.

[0050] The preparation method of the surface antioxidant liquid is as follows: add N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane with a mass of 0.45 times that of thiamine chloride pyrophosphate to a 40g / L aqueous solution of thiamine chloride pyrophosphate, stir and mix evenly, then heat to 80°C, and then slowly drop a glutaraldehyde aqueous solution with a mass of 2 times that of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane and a concentration of 20% into the obtained mixed solution while stirring; after the dropwise addition is completed, heat and react for 5 hours. After the reaction is completed, completely evaporate the liquid in the reaction product, and put the obtained solid powder into 8% acetone, stir and mix evenly to obtain the surface antioxidant liquid.

[0051] The preparation method of the organic protective agent comprises the following steps:

[0052] The first step is to add 0.7 times the mass of ethylene glycol to a 5wt% ether solution of butanol aldehyde, mix and stir evenly, then add concentrated hydrochloric acid, and react the resulting mixed components at a temperature of 125°C for 10 hours. After the reaction is completed, the resulting components are rotary evaporated, and the resulting reaction products are stored for standby use; wherein the concentration of the concentrated hydrochloric acid is 36wt%, and the amount of the concentrated hydrochloric acid used is 0.45 times the volume of the ether;

[0053] Step 2: Add 1.05 times the mass of the reaction product to a 0.06 g / mL chloroform solution of 5-methyl-1H-benzotriazole, raise the temperature to 65°C and stir to fully dissolve it, then slowly drop 1.45 times the mass of 5-methyl-1H-benzotriazole into the solution while stirring, and keep the temperature for reaction for 60 minutes after the addition is complete;

[0054] Step 3: After the reaction is completed, add a 35% volume of 3 mol / L hydrochloric acid aqueous solution to the resulting component, and keep the reaction at 50°C for 6 hours; after the reaction is completed, perform rotary evaporation on the resulting component; then mix the resulting liquid composition with anhydrous ethanol in a volume ratio of 1:5, and obtain an organic protective agent after mechanical stirring.

[0055] Example 3

[0056] A surface treatment process for electrolytic copper foil comprises the following steps:

[0057] Step 1: Place the copper foil in a degreasing tank, and add a sodium hydroxide aqueous solution with a temperature of 65°C and a concentration of 75g / L into the tank to clean and degrease the copper foil; after degreasing, wash with water, and then pickle the copper foil. After pickling, place the copper foil in a water washing tank to clean its surface; wherein the acid solution used in step 1 is a 130g / L sulfuric acid aqueous solution, and its temperature is 50°C;

[0058] Step 2: Place the copper foil treated in step 1 in a roughening tank for roughening treatment. After the roughening is completed, place the copper foil in a water washing tank for washing. 2+ The concentration of H2SO4 is 150g / L, the temperature is 45℃, and the electrolyte flow rate is 18m 3 / h; wherein, when the copper foil is roughened, the roughening current is set to 3200A and the roughening time is set to 7s;

[0059] Step 3: Place the copper foil roughened in step 2 in a curing tank for curing. After curing, place the copper foil in a water washing tank for washing. 2+ The concentration is 75g / L, the H2SO4 concentration is 130g / L, the temperature is 50℃, and the electrolyte flow rate is 20m 3 / h; wherein, when the copper foil is cured, the curing current is set to 2700A and the curing time is set to 8s;

[0060] Step 4: Place the solidified copper foil in a barrier layer treatment tank, and use a Zn-Ni-K ternary alloy treatment process to form a barrier layer on the surface of the copper foil; after water washing, immerse the copper foil in a surface antioxidant liquid at a temperature of 65°C for 10 minutes; wherein, when forming the barrier layer in step 4, Zn 2+ The concentration is 3g / L, Ni 2+ The concentration is 2g / L, K + The concentration is 110g / L;

[0061] Step 5: After the impregnation is completed, the copper foil is fished out and cleaned with anhydrous ethanol, and then the copper foil is transferred to a vacuum drying oven and vacuum dried at a temperature of 90°C;

[0062] Step 6: After vacuum drying is completed, spray the organic protective agent evenly on the surface of the copper foil and dry it at 80°C; after drying is completed, cut and package the copper foil in turn; finally, the surface treatment process of the electrolytic copper foil is completed.

[0063] The preparation method of the surface antioxidant liquid is as follows: add γ-aminopropylmethyldiethoxysilane with a mass of 0.5 times that of thiamine chloride pyrophosphate to a 45g / L aqueous solution of thiamine chloride pyrophosphate, stir and mix evenly, then heat to 85°C, and then slowly drop a glutaraldehyde aqueous solution with a mass of 2.5 times that of γ-aminopropylmethyldiethoxysilane and a concentration of 25% into the obtained mixed solution while stirring; after the dropwise addition is completed, heat and react for 6 hours, and after the reaction is completed, completely evaporate the liquid in the reaction product, and put the obtained solid powder into 10% acetone, stir and mix evenly to obtain the surface antioxidant liquid.

[0064] The preparation method of the organic protective agent comprises the following steps:

[0065] The first step is to add 0.8 times the mass of ethylene glycol to a 6wt% ether solution of butanol aldehyde, mix and stir evenly, then add concentrated hydrochloric acid, and react the resulting mixed components at a temperature of 130°C for 12 hours. After the reaction is completed, the resulting components are rotary evaporated, and the resulting reaction products are stored and reserved; wherein the concentration of the concentrated hydrochloric acid is 38wt%, and the amount of the concentrated hydrochloric acid used is 0.5 times the volume of the ether.

[0066] Step 2: Add 1.1 times the mass of the reaction product to a 0.08 g / mL chloroform solution of 5-methyl-1H-benzotriazole, raise the temperature to 70°C and stir to fully dissolve it, then slowly drop 1.5 times the mass of 5-methyl-1H-benzotriazole in toluene-2,4-diisocyanate while stirring, and keep the temperature for 70 minutes after the addition is complete;

[0067] Step 3: After the reaction is completed, add a 40% volume of 4 mol / L hydrochloric acid aqueous solution to the resulting component, and keep the reaction at 55°C for 7 hours; after the reaction is completed, perform rotary evaporation on the resulting component; then mix the resulting liquid composition with anhydrous ethanol in a volume ratio of 1:6, and obtain an organic protective agent after mechanical stirring.

[0068] Comparative Example 1: The difference between this embodiment and embodiment 1 is that in this embodiment, the copper foil is not immersed in the surface antioxidant liquid.

[0069] Comparative Example 2: The difference between this embodiment and embodiment 1 is that in this embodiment, no organic protective agent is sprayed on the surface of the copper foil.

[0070] Performance test: The electrolytic copper foil samples treated in Examples 1 to 3 and Comparative Examples 1 to 2 were placed on the same rough surface, and rubbed 50 times, 80 times, and 100 times with the same pressure and tension. The copper foils rubbed for different times were uniformly placed in moist oxygen (temperature of 25° C., humidity of 40%) for 7 days, and then the changes in the friction points on the copper foil surfaces were observed. The test data obtained are recorded in the following table:

[0071]

[0072] By comparing and analyzing the relevant data in the table, it can be seen that the electrolytic copper foil treated by the present invention not only has excellent anti-oxidation performance, but also has excellent wear resistance, which prolongs the service life of the electrolytic copper foil to a certain extent and significantly improves its quality. This shows that the surface treatment process of the electrolytic copper foil provided by the present invention has a broader market prospect and is more suitable for promotion.

[0073] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0074] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A surface treatment process for electrolytic copper foil, characterized in that: The following steps are involved: Step 1: Place the copper foil in a degreasing tank, and add a sodium hydroxide aqueous solution with a temperature of 55-65°C and a concentration of 60-75 g / L into the tank to clean and degrease the copper foil; after degreasing, wash with water, and then pickle the copper foil. After pickling, place the copper foil in a water washing tank to clean its surface; Step 2: Place the copper foil treated in step 1 in a roughening tank for roughening treatment. After the roughening is completed, place the copper foil in a water washing tank for washing. 2+ The concentration of H2SO4 is 15-30 g / L, the concentration of H2SO4 is 130-150 g / L, the temperature is 30-45 °C, and the electrolyte flow rate is 13-18 m 3 / h; Step 3: Place the copper foil roughened in step 2 in a curing tank for curing. After curing, place the copper foil in a water washing tank for washing. 2+ The concentration is 55-75 g / L, the H2SO4 concentration is 110-130 g / L, the temperature is 30-50 °C, and the electrolyte flow rate is 15-20 m 3 / h; Step 4: Place the solidified copper foil in a barrier layer treatment tank, and use a Zn-Ni-K ternary alloy treatment process to form a barrier layer on the surface of the copper foil; after water washing, immerse the copper foil in a surface antioxidant liquid at a temperature of 50 to 65° C. for 5 to 10 minutes; Step 5: After the impregnation is completed, the copper foil is fished out and cleaned with anhydrous ethanol, and then the copper foil is transferred to a vacuum drying oven and vacuum dried at a temperature of 70 to 90°C; Step 6: After vacuum drying is completed, spray the organic protective agent evenly on the surface of the copper foil and dry it at a temperature of 60-80°C; after drying is completed, cut and package the copper foil in turn; finally, the surface treatment process of the electrolytic copper foil is completed.

2. The surface treatment process of electrolytic copper foil according to claim 1, characterized in that: The acid solution used in the step 1 is a 110-130 g / L aqueous solution of sulfuric acid, and the temperature thereof is 30-50°C.

3. The surface treatment process of electrolytic copper foil according to claim 1, characterized in that: In the step 2, when the copper foil is roughened, the roughening current is set to 2900-3200A, and the roughening time is set to 4-7s.

4. The surface treatment process of electrolytic copper foil according to claim 1, characterized in that: In the step 3, when the copper foil is cured, the curing current is set to 2300-2700A, and the curing time is set to 5-8s.

5. The surface treatment process of electrolytic copper foil according to claim 1, characterized in that: In the step 4, when forming the barrier layer, Zn 2+ The concentration is 2-3 g / L, Ni 2+ The concentration is 1.5-2 g / L, K + The concentration is 90~110g / L.

6. The surface treatment process of electrolytic copper foil according to claim 1, characterized in that: The preparation method of the surface antioxidant liquid is as follows: adding a coupling agent whose mass is 0.4 to 0.5 times of the mass of the thiamine chloride pyrophosphate to a 35 to 45 g / L aqueous solution of thiamine chloride pyrophosphate, stirring and mixing evenly, heating to 75 to 85° C., and then slowly dropping a glutaraldehyde aqueous solution whose mass is 1.5 to 2.5 times of the mass of the coupling agent and whose concentration is 20 to 25% into the obtained mixed solution while stirring; after the dropping is completed, keeping the temperature for reaction for 4 to 6 hours, after the reaction is completed, completely evaporating the liquid in the reaction product, and putting the obtained solid powder into 7 to 10 mass of acetone, stirring and mixing evenly to obtain the surface antioxidant liquid.

7. The surface treatment process of electrolytic copper foil according to claim 6, characterized in that: The coupling agent is selected from any one of γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane and γ-aminopropylmethyldiethoxysilane.

8. The surface treatment process of electrolytic copper foil according to claim 1, characterized in that: The preparation method of the organic protective agent comprises the following steps: The first step is to add 0.6 to 0.8 times the mass of butanol aldehyde into a 4 to 6 wt % ether solution of butanol aldehyde, add concentrated hydrochloric acid after mixing and stirring evenly, and react the resulting mixed components at a temperature of 120 to 130° C. for 8 to 12 hours. After the reaction is completed, the resulting components are subjected to rotary evaporation, and the resulting reaction products are stored and reserved; Step 2: Add 1.05-1.1 times the mass of the reaction product to a 0.05-0.08 g / mL chloroform solution of 5-methyl-1H-benzotriazole, raise the temperature to 60-70°C and stir to fully dissolve it, then slowly drip 1.4-1.5 times the mass of 5-methyl-1H-benzotriazole toluene-2,4-diisocyanate while stirring, and keep the temperature for 50-70 minutes after the addition is complete; Step 3: After the reaction is completed, add a 30-40% volume of hydrochloric acid aqueous solution with a concentration of 2-4 mol / L to the resulting component, and keep the reaction at a temperature of 45-55°C for 5-7 hours; after the reaction is completed, perform rotary evaporation on the resulting component; then mix the resulting liquid composition with anhydrous ethanol in a volume ratio of 1:4-6, and obtain an organic protective agent after mechanical stirring.

9. The surface treatment process of electrolytic copper foil according to claim 8, characterized in that: The concentration of concentrated hydrochloric acid in the first step is 36-38 wt %, and the amount of concentrated hydrochloric acid used is 0.4-0.5 times the volume of ether.

Citation Information

Patent Citations

  • Surface processing technology improving high-temperature stripping-resisting performance of electrolytic copper foil

    CN105018978A

  • Copper foil surface chromic anhydride passivating treatment process

    CN110219035A

  • Surface treatment process of reverse electrolytic copper foil for flexible copper-clad plate

    CN114481245A

  • Production method for high heat-resistant electrodeposited copper foil

    WO2022041533A1